2014
DOI: 10.1590/s1677-5538.ibju.2014.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and prevalence of erectile dysfunction in hemodialysis patients

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: The proposal of this study was to determine the prevalence and the associated factors of erectile dysfunction (ED) among hemodialysis (HD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
(49 reference statements)
3
11
0
2
Order By: Relevance
“…The study sample was similar to those of other epidemiological studies, with a mean age of 53.3 years and association of ED with chronic diseases ( 1 , 6 , 24 ). In agreement with Araújo et al, 2004 ( 25 ), we also observed poorer erection with aging.…”
Section: Discussionsupporting
confidence: 78%
“…The study sample was similar to those of other epidemiological studies, with a mean age of 53.3 years and association of ED with chronic diseases ( 1 , 6 , 24 ). In agreement with Araújo et al, 2004 ( 25 ), we also observed poorer erection with aging.…”
Section: Discussionsupporting
confidence: 78%
“…However, the crude prevalence of erectile dysfunction was over 50% among men with diabetes [ 8 ]. In the study conducted in Israeli, the prevalence of ED was 57% [ 9 ], in china 90.9% [ 10 ], in India approaching 50% in both type 1 and type 2 DM [ 11 ], in Vietnam 66.9% [ 12 ], in Brazil 66.19% [ 13 ] and Iran 59.5% of type 2 DM patients [ 14 ]. According to the studies done in African countries the prevalence of ED was 71.1% in Nigeria [ 15 ], 48% in Guinea [ 16 ], 85.7% in Egypt [ 17 ], 95% in South Africa [ 18 ], 68.8% in Kenya [ 19 ], 74.1% in Ivory Coast [ 20 ], 74% in Nigeria [ 21 ], 73.9% in Zimbabwe [ 22 ], 94.7% in Nigeria, 36.0% in South Africa [ 23 ], 55.1% in Tanzania with 12.8% of participants suffering from mild dysfunction, 11.5% from moderate, and 27.9% from severe Dysfunction [ 3 ], and 69.9% Tigray Ethiopia with 32.9% suffering from mild, 31.7% moderate, and 5.2% severe erectile dysfunction [ 2 ]..…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] It is more common in patients with chronic kidney disease and those on HD, occurring in more than 80% of patients. [5] The frequency of ED (76.9%) was high among HD patients compared to reports from Spain, [7,8] The Netherlands, [3] and Brazil, [9] although it was comparable to other reports from the USA (82%), [2] Sudan (83%), [5] Saudi Arabia (82.7%), [10] Iran (87.7%), [11] Brazil (86.4%), [12] and Egypt (82.5%). [13] Older age was shown to be associated with ED in communitybased studies [6] and also among HD patients.…”
Section: Discussionmentioning
confidence: 89%